2021
DOI: 10.1007/s00415-021-10530-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI correlates of cognitive improvement after home-based EEG neurofeedback training in patients with multiple sclerosis: a pilot study

Abstract: Objective Neurofeedback training may improve cognitive function in patients with neurological disorders. However, the underlying cerebral mechanisms of such improvements are poorly understood. Therefore, we aimed to investigate MRI correlates of cognitive improvement after EEG-based neurofeedback training in patients with MS (pwMS). Methods Fourteen pwMS underwent ten neurofeedback training sessions within 3–4 weeks at home using a tele-rehabilitation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…BCIs allow for device control without motor involvement as they translate brain activation into output signals for communication or environmental control [ 7 ], and the sensorimotor rhythm (SMR) based BCIs detect characteristic changes in SMR in response to the motor task. The SMR based on BCIs training was adopted in several studies [ 8 10 ]. SMRs can be measured over the sensorimotor cortex (SMC) and modulated by motor imagery (MI), motor attempt (MA), or motor execution (ME) tasks [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCIs allow for device control without motor involvement as they translate brain activation into output signals for communication or environmental control [ 7 ], and the sensorimotor rhythm (SMR) based BCIs detect characteristic changes in SMR in response to the motor task. The SMR based on BCIs training was adopted in several studies [ 8 10 ]. SMRs can be measured over the sensorimotor cortex (SMC) and modulated by motor imagery (MI), motor attempt (MA), or motor execution (ME) tasks [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was possible to verify the presence of the use of neuroimaging techniques such as fMRI, as an auxiliary way of evaluating the results (Shindo et al, 2011 ; Pinter et al, 2021 ). With regard to the presence of Follow-up, it is noted that after the interventions of the 44 studies analyzed, only 12 studies carried out the follow-up ( Figure 3 ) (Hammer et al, 2011 ; Shindo et al, 2011 ; Schabus et al, 2017 ; Marlats et al, 2020 ; Lau et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In studies with patients diagnosed with Multiple Sclerosis, the presence of improvement in cognitive functions was seen, such as in short- and long-term verbal memory, short-term visuospatial memory, working memory, and in the functional connectivity of patients with Multiple Sclerosis (Kober et al, 2019 ; Pinter et al, 2021 ). Hammer et al ( 2011 ), showed improvements in the quality of sleep of patients with insomnia after neurofeedback training, but, such improvements were not visualized by Schabus et al ( 2017 ), not being more efficacious than Cognitive Behavioral therapy.…”
Section: Resultsmentioning
confidence: 99%
“…In BCI technology, EEG signals can be used to objectively and accurately detect the brain specificity of patients with cognitive impairment, which could be performed in the community or even at home (PoŽar et al, 2020 ; San-Juan et al, 2020 ; Pinter et al, 2021 ). VR technology provides an immersive environment for patients with cognitive impairment, improves patient participation and training effect (Snider et al, 2013 ; Appel et al, 2020 ; Bauer and Andringa, 2020 ; Mancuso et al, 2020 ; Thielbar et al, 2020 ).…”
Section: Bci-vr Strategy For Evaluating and Rehabilitating Covid-19 Patients With Cognitive Impairmentmentioning
confidence: 99%
“…The rapid development of a brain-computer interface (BCI), virtual reality (VR), and artificial intelligence has promoted the diagnosis and treatment of cognitive impairment in the direction of intellectual development. Studies have shown that BCI-VR technology can compensate for the limitations of BCI alone and provide new rehabilitation and assessment methods for patients with cognitive impairment, which has attracted increasing attention (Wen et al, 2018 , 2020 ; Bauer and Andringa, 2020 ; Mancuso et al, 2020 ; Pinter et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%